UJI PRAKTIKALITAS PERANGKAT EKSPERIMEN OERSTED SEBAGAI MEDIA PEMBELAJARAN FISIKA DI SMA - Gagas Prakarsa; Zulirfan Zulirfan; Azizahwati Azizahwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: This study aimed to know the practicality level of Oersted experimental devices. This devices consist of experimental tool and Oersted experimental guidebook which were used as physics learning media in magnetism topic for senior high school students. The respondents of this research were 4 teachers and 30 of XII grade students from SMAN 1 Kampar and MAN 1 Pekanbaru. The data were obtained by using questionnaires which were given to the students after using the experimental devices. Descriptive analysis showed that the practicality of experimental devices was in very high category (mean scores 3,55 and 3,93). The analysis toward the parcticality of experimental guidebook was also categorized very high (mean scores: 3.64 dan 3.85). Based on that, Oersted experimental devices can be declared practical and eligible to use as physics learning media for senior high school studentsKey Words : Magnetism, Practicality, Oersted experimental devices.